Best orthogonal trigonometric approximations of the classes $B^{Ω}_{p,θ}$ of periodic functions of many variables - Voitenko, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain exact-order estimates for the best orthogonal trigonometric approximations of the classes $B^{Ω}_{p,θ}$ of periodic functions of many variables in the space $L_q$.